Amino acid alterations in fibronectin binding protein A (FnBPA) and bacterial genotype are associated with cardiac device related infection in Staphylococcus aureus bacteraemia. Issue 2 (February 2015) - Hos, Nina J.; Rieg, Siegbert; Kern, Winfried V.; Jonas, Daniel; Fowler, Vance G.; Higgins, Paul G.; Seifert, Harald; Kaasch, Achim J.
Summary Objectives Staphylococcus aureus initiates cardiac device-related infection (CDI) by binding of fibronectin binding protein A (FnBPA) to the device's surface. In FnBPA, specific "binding enhancing" amino acid alterations are associated with CDI. However, no study has investigated whether these mutations also occur in geographically different regions and whether they arise during infection or are inherent properties of the infecting isolate. Methods We analysed bacterial isolates from 34 patients with S. aureus bacteraemia and implanted cardiac devices for association with CDI, FnBPA sequence, classification into a clonal complex (CC), and binding to fibronectin (Fn). Results We confirmed that amino acid alterations at positions 652, 782, and 786 in FnBPA were associated with CDI (p = 0.005). Furthermore, CC15 and CC45 isolates were associated with CDI (p = 0.004). All isolates within a CC exhibited a characteristic mutation pattern, with major changes occurring in CC45 including a duplication of D1 and an altered immunogenic epitope in the D3 repeat. Isolates harbouring the "binding enhancing" mutations showed a slightly increased Fn binding capability, whereas Fn binding was decreased in CC45 isolates, according to a microtiter plate assay. Conclusions FnBPA sequence variations are lineage specific and display inherent properties of the infecting isolate. Sequence analysis of FnBPA, as well as the bacterial genotype, may be used to predict the risk for device-related infection.